The Effect of Transformational Principal Leadership and ERG-Based Teacher Motivation on Teacher Performance - Rachmat Nurhidayat; Arnidah; Pada, Amir (Jurnal Sains Sosio Humaniora, 2025)
Teacher performance plays a crucial role in determining the quality of educational outcomes, particularly at the primary school level. Previous studies have emphasized the importance of school leadership and teacher motivation; however, empirical research integrating transformational leadership and ERG-based motivation remains limited. This study aims to examine the effect of transformational principal leadership and teacher work motivation based on ERG theory on teacher performance. A quantitative ex post facto design was employed, involving all 17 teachers of a public primary school in Makassar, Indonesia, using a census sampling technique. Data were collected through validated and reliable questionnaires and analyzed using multiple linear regression. The results indicate that transformational principal leadership has a significant positive effect on teacher performance (p = 0.011), while teacher work motivation also significantly influences teacher performance (p = 0.038). Simultaneously, both variables significantly affect teacher performance, explaining 68.3% of the variance (Adjusted R² = 0.683). These findings suggest that strengthening transformational leadership practices and fulfilling teachers’ existence, relatedness, and growth needs are essential strategies for enhancing teacher performance. The study contributes to educational management literature by empirically confirming the synergistic role of leadership and motivation in improving teacher performance.